Green synthesis, characterization and antibacterial activity of silver nanoparticles by Malus domestica and its cytotoxic effect on (MCF-7) cell line. (October 2019) - Mariadoss, Arokia Vijaya Anand; Ramachandran, Vinayagam; Shalini, Vijayakumar; Agilan, Balupillai; Franklin, Jebaraj Herbert; Sanjay, Kumar; Alaa, Y. Ghidan; Tawfiq, M. Al-Antary; Ernest, David
Abstract: This article reports the utilization of Malus domestica for the synthesis of silver nanoparticles (AgNPs) with cytotoxic activity against the Michigan Cancer Foundation-7 (MCF-7) cell line as well as their antibacterial and radical scavenging potential. The biosynthesized AgNPs were confirmed using various analytical characterization techniques. The cytotoxic effect of Malus domestica- AgNPs ( M.d- AgNPs) was studied by MTT assay and scavenging efficacy was assessed by DPPH, nitric oxide radical and phosphomolybdate assays. Furthermore, green synthesized nanoparticles were evaluated for their antibacterial activity against multidrug resistant-clinical isolates. M.d- AgNPs were observed to be almost spherical in shape with an average diameter from 50 to 107.3 nm as assessed by TEM and DLS. M.d- AgNPs revealed the dose-dependent antioxidant activity and antimicrobial activity against multidrug-resistant bacterial strain viz. Enterobacter aerogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli . Also, in vitro studies revealed dose-dependent cytotoxic effects of M.d- AgNPs treated MCF-7 cell line. The data strongly suggest that M.d- AgNPs had a potential antioxidant, antimicrobial and cytotoxicity activity. Highlights: Simple, Cost effective and eco-friendly green synthesis of AgNPs from M.domestica . The synthesized M.d -AgNP solution was stable for more than three months. Antimicrobial efficacy was demonstrated against multidrug-resistant human pathogenic bacteria. M.d -AgNPs exhibited notable anticancer activity in MCF-7 cell line model.